Standing up, Fighting Back: Fostering Collective Action in CUPE New Brunswick, 1963-1993 - Vinh-Doyle, William (University of New Brunswick, 2015)
The emergence of the Canadian Union of Public Employees (CUPE) in the 1970s as the largest union in Canada was a major development in Canadian labour history and the result of extensive efforts to organize unorganized civil servants and public employees. Public sector union growth has often been thought to have differed fundamentally from the experience of private sector unions, on the grounds that union rights were extended to public sector workers without struggle. The history of CUPE New Brunswick, established in 1963, and its predecessor unions in the 1950s demonstrates the complex struggles of civil servants and public employees to acquire and then to apply collective bargaining rights in the province of New Brunswick. While the enactment of the Public Service Labour Relations Act (PSLRA) in 1968 provided a legal means for civil servants to join a union and bargain collectively, public sector workers continued to struggle for improved wages and working conditions throughout the 1970s and 1980s. These conflicts, which drew on both membership mobilization and legal strategies, are shown in detail in the experience of CUPE members in Local 963, New Brunswick Liquor Store Workers, and Local 1252, New Brunswick Council of Hospital Unions, the umbrella organization representing hospital support workers. While locals within CUPE New Brunswick worked independently of one another, the more than 200 CUPE locals in the province joined together in 1992 to resist measures introduced by the provincial Liberal government. While this was essentially a defensive struggle to protect existing rights, it also represented a challenge to the emerging policies of neo-liberalism and a culmination of a tradition of collective action within the union.